Biocompatible graphite-coated electrodes for sustainable plant-based energy harvesting - Rahman, Sk Rakibur; Ngu, Eng Eng; Chung, Gwo Chin; Pang, Wai Leong; Tan, Kar Ban; Kumar Singh, Ajay; Ashraf, Muhammad Aqeel; Chan, Kah Yoong (Taylor and Francis Ltd., 2026)
The environmental effects of fossil fuel consumption have continued to promote research in other energy sources that are more eco-friendly and can be sustained in the long run. One of the promising energy harvesting methods is plant-based energy harvesting, which has been considered a potential approach in developing energy harvesting systems for low-power applications, such as precision agriculture, environmental monitoring, and IoT sensor networks. The present research aimed to evaluate the potential of long-term energy harvesting using an Aloe vera plant, considering its health and the biocompatibility of electrodes. There was a challenge when uncoated zinc (Zn) and copper (Cu) electrodes emitted toxic ions (Zn2+ and Cu2+) that initiated foliar desiccation, tissue necrosis, and physiological degradation. Graphite-coated electrodes were henceforth brought in as biocompatible alternatives for reducing ion leakage while maintaining electrical conductivity. A commercially used wound-healing agent was also applied at sites of electrode insertion to facilitate tissue conservation. The health of the plants and energy harvesting were monitored over a period of 7 days. The results of this research have shown that material modification and application of a wound-healing agent have a positive effect on plant health without compromising energy harvesting.